Scoring Model in Operational Research on Cultural-Tourism: A Case Study in Kota Kinabalu, Sabah - Thavamalar Ramamoorty; Noraini Abdullah; Suzelawati Zenian (2020)
The predominant culture of Sabah consists of a motley of cultures, each of which has been brought in by the different ethnic groups from their indigenous cultures. The total population of Sabah consists of more than thirty different ethnicities and races, and the number of languages and dialects go over eighty. Hence the cultural tourism in Sabah would have varied criteria that can be looked into. The aim of this paper is to use the scoring model in operational research to rank these decision criteria according to highest scores. The preferability of tourist visiting these hot spots is done by ranking their preferability based on a weightage. Highly scored attraction factors would attract more tourists to visit cultural spots in Kota Kinabalu. Therefore, these would help operational managers in the tourism industry to focus on promoting and marketing this sector.